Lebanon's heartbreaking predicament - Saikal, Amin (2022)
Lebanon is in a dire situation. It is in a most difficult phase of its evolution as an independent state since the mid-1940s. Unless its system of governance is changed and regional interference is stopped, the country’s future looks very bleak.